Haemorrhagic enteritis in newborn calves associated with Clostridium perfringens and colostrum delivery. Issue 4 (27th August 2015) - Valgaeren, Bonnie R.; Pardon, Bart; Verherstraeten, Stefanie; Goossens, Evy; Timbermont, Leen; Haesebrouck, Freddy; Ducatelle, Richard; Van Immerseel, Filip; Deprez, Piet
Abstract : Introduction: This report describes 13 cases of fatal haemorrhagic enteritis in newborn calves. Case presentation: Clostridium perfringens type A was isolated both from the intestinal contents of seven calves and from three visibly worn and soiled bucket teats and stomach tubes used for colostrum administration. After replacement of the colostrum delivery device and introduction of hygienic measures, no new cases appeared on any of the farms. Conclusion: The results suggested that contamination of colostrum with C. perfringens caused these cases of neonatal haemorrhagic enteritis.